The Study of Neutrino Oscillations with Emulsion Detectors - A. Ereditato (Advances in High Energy Physics)
Particle detectors based on nuclear emulsions contributed to the history of physics with fundamental discoveries. The experiments benefited from the unsurpassed spatial and angular resolution of the devices in the measurement of ionizing particle tracks and in their identification. Despite the decline of the technique around the 1970’s caused by the development of the modern electronic particle detectors, emulsions are still alive today thanks to the vigorous rebirth of the technique that took place around the beginning of the 1990’s, in particular due to the needs of neutrino experiments. This progress involved both the emulsion detectors themselves and the automatic microscopes needed for their optical scanning. Nuclear emulsions have marked the study of neutrino physics, notably in relation to neutrino oscillation experiments and to the related first detection of tau-neutrinos. Relevant applications in this field are reviewed here with a focus on the main projects. An outlook is also given trying to address the main directions of the R&D effort currently in progress and the challenging applications to various fields.